The Law and Economics of Canadian Competition Policy - Trebilcock, M. J. (Book collections on Project MUSE., 2002)
Offering a unique cross-disciplinary approach to scholarship in law and economics, this much-needed work expounds and critically evaluates all of the major doctrines of Canadian competition policy. The topics addressed, each in a separate chapter, include: Canadian competition policy in an historical context; basic economic concepts; multi-firm conduct; horizontal agreements; the merger review process; predatory pricing and price discrimination; vertical restraints; intra-brand competition; inter-brand competition; abuse of dominance; competition policy and intellectual property rights; competition policy and trade policy; competition policy and regulated industries; and enforcement. The treatment of each substantive topic is organized first around a discussion of the relevant body (or bodies) of economic theory and then the pertinent bodies of legal doctrine, including case law. Each chapter contains a critique of existing law in light of contemporary economic theory. This is the only book available that offers an up-to-date integrated analysis of economic theory and legal doctrine in the context of Canadian competition policy.